Functional regionalization of the differentiating cerebellar Purkinje cell population occurs in an activity-dependent manner - Dorigo, Alessandro; Valishetti, Komali; Hetsch, Florian; Matsui, Hideaki; Meier, Jochen C.; Namikawa, Kazuhiko; Köster, Reinhard W. (Frontiers in Molecular Neuroscience, 2023)
The cerebellum is organized into functional regions each dedicated to process different motor or sensory inputs for controlling different locomotor behaviors. This functional regionalization is prominent in the evolutionary conserved single-cell layered Purkinje cell (PC) population. Fragmented gene expression domains suggest a genetic organization of PC layer regionalization during cerebellum development. However, the establishment of such functionally specific domains during PC differentiation remained elusive. We show the progressive emergence of functional regionalization of PCs from broad responses to spatially restricted regions in zebrafish. Moreover, we reveal that formation of new dendritic spines during cerebellar development parallels the time course of functional domain development. Inhibition of PC neuronal activity results in reduced PC dendritic spine density and an altered stagnant pattern of functional domain formation in the PC layer. Hence, our study suggests that functional regionalization of the PC layer is driven by physiological activity of maturing PCs themselves.